Kondisi Awal Perkuliahan IPA SMP/MTS Kelas IX dalam Rangka pengembangan Alat Peraga Berbasis Project Based Learning - Silvi Yulia Sari; Wahyuni Satria Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
This study aims to analyze preliminary data on lecture conditions as the needs in developing science teaching aids. This research is the initial stage of research and development using the development model proposed by Plomp, namely preliminary research. Data collected by using questionnaire given to physics education students semester July-December 2017. Data analysis technique used in the form of descriptive statistical analysis.The results of this study are: 1) the available teaching materials are quite varied, 2) the assignments given in lectures can help students in understanding the material, 3) control of ideas and project work in lectures is still lacking, so students have limitations to develop their creativity, and 4)the students have considerable potential in understanding the material, but the number of students who have ideas in solving problems and who are able to correct friends' answers, and those who actively ask are still low.It can be conclude that the development science teaching aids based on project-based learning need to be done to improve student creativity.